PLANT OILS AND FATS: THEIR BIOCHEMICAL CONSEQUENCES IN RODENT MODELS - Al-Saad, Mohanad Ali Kareem; Al-Amiri , Mohanad Tariq Hussein (International Research Journal Diagnostics, 2024)
Fatty acids, known for their hydrocarbon chains spanning between 4 and 36 carbons, play a crucial role in various biological processes. Natural fats primarily consist of straight-chain fatty acids with an even number of carbon atoms. Fatty acid synthesis, or lipogenesis, predominantly occurs in the cytosol and is essential for several tissues, including the liver, kidneys, brain, and adipose tissue. The rate of lipogenesis is closely tied to an organism's nutritional status, increasing in well-fed animals with a high-carbohydrate diet and decreasing under caloric restriction or insulin deficiency, such as in diabetes mellitus. Cholesterol, a key sterol, exists in animal tissues in the form of lipoproteins and free cells, or as esters in the bloodstream. Cholesterol esters serve as a common storage and transport form, while free cholesterol often transforms into bile acids. Unsaturated fatty acids within cell membrane phospholipids play a vital role in maintaining membrane fluidity. HighDensity and Low-Density Lipoproteins (HDL and LDL) are essential in transporting cholesterol to and from the liver. HDL, often referred to as "good cholesterol," aids in cholesterol exchange and its elimination in the bile. Clinical disorders related to fatty acid metabolism primarily involve oxidation processes, with triacylglycerides being the most prevalent lipid family, consisting of fatty acids and glycerol and serving as a major storage lipid.